What was the Impact of Creating Better Jobs for More People in China’s Economic Transformation? What We Know and Questions for Further Investigation - Merotto, Dino; Jiang, Hanchen (World Bank, Washington, DC, 2021)
The authors show that for China the movement of more people into better jobs with higher incomes formed a very important explanation for the country’s long-term success in growth and poverty reduction. China’s exporting cities created a virtuous cycle of new wage-employment-creating investments by new businesses making new products. The rapid increase in urban labor demand drew hundreds of millions of workers from the rural “traditional” sector to the “modern” sector, providing them with more reliable waged incomes. This dramatically raised the share of waged employment in China’s economy and unleashed new middle-class demand for more income-elastic goods and services. Growth in urban wages was moderated by regulated rural to urban labor migration under the Hukou system. This raised returns to capital, which maintained business incentives to re-invest their profits in new goods and services for which new markets were opening. Production of cheaper manufactured goods for the world market was an important catalyst, but domestic demand for services in China has maintained the momentum.